Reading and rewriting poetry on life to survive the COVID-19 pandemic. Issue 2 (3rd April 2021) - Sharma, Daneshwar
ABSTRACT: The pandemic COVID-19 has changed every aspect of human life. Lockdowns have halted the ever-throbbing heart of humanity. As we become prisoners in our homes, the age-old habit of looking at life, inside and outside, has changed. As humans, globally and collectively, suffered the zoo-like caging for the first time in the history of humankind, Nature, in the absence of her biggest polluter, started healing. After a long, rampant, unmindful industrialization era, animals, birds, fish felt free for the first time to roam around and reclaim their territory. In these troubled times, I look toward poetry as a means to understand the changes happening due to the pandemic. I see the pandemic crisis and its aftereffects from a personal point of view, as a father and as a working-class male, and from a social point of view as a human being.